Decision support system for giving rewards to Asmika and Areka teachers using the saw method - Nera Mayana Br Tarigan; Eviyanti Br Barus; Fretty Wandani Br Ginting; Oktavia Tumangger (Jurnal Info Sains : Informatika dan Sains, 2024)
Rewards are given to appreciate the work or performance of a person or team. Research was conducted to provide rewards to Asmika and Areka teachers using the SAW method. This research applies the SAW method where giving rewards often causes debate due to differences of opinion. So that the decision to give rewards can be made appropriately and by the criteria that have been set. Research Method, namely the survey research method, is a research method carried out using surveys or direct data collection from interested parties. The method used to analyze the data is the SAW method. This research aims to apply the SAW method in giving rewards to ASMIKA and AREKA teachers and to design and build a decision support system for giving rewards to ASMIKA and AREKA teachers. This research targets the results of the application for giving rewards to ASMIKA and AREKA teachers where the research results will be published in the Sinta journal. The results of the research on the application of the SAW method of giving rewards to Asmika and Areka teachers began with determining criteria, alternative, and Crips data as sub-criteria. Rewards are given if the results of the analysis of alternative data get a value >=80. The research found the conclusion that one alternative received a reward, namely A4, while A1, A2, A3, and A5 had not yet received a reward. The SAW method can be applied to the process of giving rewards to Asmika and Areka teachers.